Paracelsus Historisch-kritische Ausgabe - Schnitzler, Arthur (Werke in historisch-kritischen Ausgaben, 2021)
At the center of Schnitzler's one-act verse drama Paracelsus, written between 1894 and 1898 and set in sixteenth-century Basel, is a hypnosis experiment that blurs the boundaries between dream and reality. This historical critical edition documents the text's genesis and print history, and provides manuscript facsimiles including transcriptions, a critically reviewed printed text with a variants apparatus, and a commentary.